The OECD as a Booster of National School Governance. The case of New Math in Sweden, 1950-1975 - Johan Prytz (FahrenHouse, 2020)
New Math was an international reform movement aimed at thorough changes in school mathematics with respect to both content and teaching methods. This movement started to gain influence in the 1950s, and in the 1960s several countries prepared and implemented their own New Math reforms. This movement not only attracted prominent mathematicians and psychologists but also garnered support from the Organization of Economic Co-operation and Development (OECD). The New Math reforms are examples of how OECD supported thorough and broad changes in national systems of education. In most countries, however, the influence of New Math on syllabi began to fade by the 1970s. In this paper, I discuss how the New Math in Sweden reform boosted national governance and changed power relations between the teachers, textbook producers, and the national school administration. I also suggest that OECD continued to support this power structure through the testing enterprises associated with PISA.